Understanding consumer data use in new product development and the product life cycle in European food firms – An empirical study. (September 2019) - Horvat, Andrijana; Granato, Giulia; Fogliano, Vincenzo; Luning, Pieternel A.
Highlights: Empirical study on consumer data use in product development in European food firms. Three consumer data types: consumer involvement, food trends, environmental factors. More than 85% of respondents use all three data types in new product development. Respondents much rarely use consumer data in the product life-cycle. Data collection methods do not optimally support development of truly new products. Abstract: New food products have a high chance of market failure. To improve the chances of new product success, a consumer-oriented approach to product development has been recommended. The approach emphasizes the importance of an optimal fit between consumers' needs and the new product. To achieve this goal, food professionals generate and use various consumer data types and methods. However, very few studies address the extent to which the food industry uses consumer data in product development. This study investigated to what extent European food firms use various consumer data in different phases, i.e., new product development (NPD) and the product life cycle (PLC), and what data collection methods they employ. The current study classified consumer data into three types: consumer involvement, food trend, and environmental factor data. The results showed that more than 85% of the respondents use all three data types in NPD, while they rarely use consumer data in the PLC. Respondents most frequently use data collection methods such as focus groups, consumer surveys, and indirect data collection (e.g., internet, magazines). These methods are less effective in assuring product success and in developing new-to-the-world products. In fact, more than half of the respondents never or rarely worked on new-to-the-world projects. Increasing the use of consumer data in the PLC and adapting data collection methods to the type of the project and the phase of product development present opportunities for food firms to improve chances of new product success.